Seasonal Variation of Testosterone Levels in a Large Cohort of Men. (22nd June 2022) - Zornitzki, Taiba; Tshori, Sagi; Shefer, Galit; Mingelgrin, Shira; Levy, Carmit; Knobler, Hilla
Abstract : Context . Various data suggest seasonal variation in testosterone levels. However, previous studies are limited by their size or by variability in baseline characteristics. Objectives . The aim of the study was to evaluate in a large cohort of males with a wide range of age, metabolic status, and coexistent morbidities whether month of blood test performance was associated with total and bioavailable testosterone levels independent of age, body mass index (BMI), existing cardiovascular disease (CVD), and CVD risk factors. Methods . Cross-sectional study includes data from computerized medical records of 27, 328 men aged 20–70, treated by the largest healthcare organization in Israel, who had undergone testosterone measurement. In 7, 940 subjects with available sex-hormone-binding globulin levels, bioavailable testosterone was calculated. Results . Total and bioavailable testosterone levels gradually decreased with age and BMI (P < 0.001 ) and were significantly lower in men with diabetes, hypertension, hyperlipidemia, and known CVD, but were higher in current smokers compared with nonsmokers (P < 0.001 ). Hormone levels were highest in August-October declined after and lowest in March. Overall, both total and bioavailable testosterone levels were significantly lower in March compared to August-October (P < 0.001 ). In a linear regression analysis, age, BMI, current smoking, and month of testing were independently associated with total (P < 0.001 ) and bioavailable testosterone levels (P = 0.002 ), and diabetes was associated with total testosterone (P < 0.001 ). Conclusion . In a large cohort of men with a wide range of age, BMI, and comorbidities, month of testing was independently associated with total and bioavailable testosterone levels. These data provide strong evidence that seasonal variation has to be considered in clinical practice.